KARAKTERISTIK KEAKURASIAN DAN KEPRESISIAN GPS PRECISE POINT POSITIONING - T. Lando, Asiyanthi
Abstrak: GPS Precise Point Positioning or PPP is a development of conventional absolute positioning method, where the advantages of this GPS PPP are using carrier phase data and pseudorange, and also using precise ephemeris and precise clocks from IGS (International GPS Service). The other advantages of GPS PPP : only using one GPS receiver so more effective and efficient, do not need base stasion, baseline, and network, and the solution can be obtained from the internet. The scope of this research is to know how far the accuracy and precision of GPS PPP is influenced by the spatial and temporal variation, time and span of observation. The solution of GPS PPP external is derived from the web-based GPS data processing service in the internet (external). The achievable from this research : the accuracy and precision level of GPS PPP in the order of centimetre (cm) to decimetre (dm) level, that have spatial and temporal variation. In the spatial variation, the lowest accuracy and precision level is in polar region and in the southern hemisphere. In the temporal variation, the accuracy and precision level is not influenced by the sunspot cycle and the season because using dual frequency data. By this GPS PPP accuracy and precision in centimetre (cm) to decimetre (dm) level, the GPS PPP method is suitable for survey and mapping application with cm - dm accuracy and precision level.